2016
DOI: 10.1007/s10909-016-1516-x
|View full text |Cite
|
Sign up to set email alerts
|

Calculation of Leggett–Takagi Relaxation in Vortices of Superfluid $$^{3}$$ 3 He-B

Abstract: We calculate the relaxation of Brinkman-Smith mode via Leggett-Takagi relaxation in the presence of an isolated vortex in superfluid 3 He-B. The calculation is based on an analytical solution of the order parameter far from the vortex axis. We obtain an expression for the dissipated power per vortex length as a function of the tipping angle of the magnetization and the orientation of the static magnetic field with respect to the vortex.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 11 publications
(36 reference statements)
0
6
0
Order By: Relevance
“…Both the present model of spin wave radiation and the Leggett-Takagi relaxation calculated in Ref. [7] give absorption that is quadratic in the coefficient C 1 and C 2 . These coefficients are solely determined by the structure of the vortex core.…”
Section: Comparison With Experimentsmentioning
confidence: 58%
See 4 more Smart Citations
“…Both the present model of spin wave radiation and the Leggett-Takagi relaxation calculated in Ref. [7] give absorption that is quadratic in the coefficient C 1 and C 2 . These coefficients are solely determined by the structure of the vortex core.…”
Section: Comparison With Experimentsmentioning
confidence: 58%
“…This mechanism seems to be most effective at temperatures close to the transition temperature T c . We find [7] that the Leggett-Takagi relaxation is too weak to explain the relaxation observed by Kondo et al Another well known relaxation mechanism arises from diffusion of the normal component of the * sami.laine@oulu.fi magnetization. It seems, however, that its contribution has to be small in the experiments by Kondo et al since the observed magnetic field dependence [5] is opposite to the one expected for spin diffusion.…”
Section: Introductionmentioning
confidence: 60%
See 3 more Smart Citations